Paediatric Trauma Score as a non-imaging tool for predicting intracranial haemorrhage in patients with traumatic brain injury - Heoung Jin Kim; Sohyun Eun; Seo Hee Yoon; Moon Kyu Kim; Hyun Soo Chung; Chungmo Koo (Scientific Reports, 2021)
Abstract To identify a useful non-imaging tool to screen paediatric patients with traumatic brain injury for intracranial haemorrhage (ICH). We retrospectively analysed patients aged < 15 years who visited the emergency department with head trauma between January 2015 and September 2020. We divided patients into two groups (ICH and non-ICH) and compared their demographic and clinical factors. Among 85 patients, 21 and 64 were in the ICH and non-ICH groups, respectively. Age (p = 0.002), Pediatric trauma score (PTS; p < 0.001), seizure (p = 0.042), and fracture (p < 0.001) differed significantly between the two groups. Factors differing significantly between the groups were as follows: age (odds ratio, 0.84, p = 0.004), seizure (4.83, p = 0.013), PTS (0.15, p < 0.001), and fracture (69.3, p < 0.001). Factors with meaningful cut-off values were age (cut-off [sensitivity, specificity], 6.5 [0.688, 0.714], p = 0.003) and PTS [10.5 (0.906, 0.81), p < 0.001]. Based on the previously known value for critical injury (≤ 8 points) and the cut-off value of the PTS identified in this study (≤ 10 points), we divided patients into low-risk, medium-risk, and high-risk groups; their probabilities of ICH (95% confidence intervals) were 0.16–12.74%, 35.86–89.14%, and 100%, respectively. PTS was the only factor that differed significantly between mild and severe ICH cases (p = 0.012). PTS is a useful screening tool with a high predictability for ICH and can help reduce radiation exposure when used to screen patient groups before performing imaging studies.